2009
DOI: 10.1021/jm9001764
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Staphyloxanthin Virulence Factor Biosynthesis in Staphylococcus aureus: In Vitro, in Vivo, and Crystallographic Results

Abstract: The gold color of Staphylococcus aureus is derived from the carotenoid staphyloxanthin, a virulence factor for the organism. Here, we report the synthesis and activity of a broad variety of staphyloxanthin biosynthesis inhibitors that inhibit the first committed step in its biosynthesis, condensation of two farnesyl diphosphate (FPP) molecules to dehydrosqualene, catalyzed by the enzyme dehydrosqualene synthase (CrtM). The most active compounds are phosphonoacetamides that have low nanomolar Ki values for CrtM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 24 publications
1
86
0
Order By: Relevance
“…In addition, we included phosphonosulfonates and related systems known to inhibit head-to-head prenyl synthases (22)(23)(24) such as dehydrosqualene synthase and squalene synthase (31), which could also inhibit Plasmodium phytoene synthase, and cationic species (such as Ro 48-8071 and quinuclidines), some of which are known to inhibit Plasmodium cell growth (28,32). The structures of all 560 compounds are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we included phosphonosulfonates and related systems known to inhibit head-to-head prenyl synthases (22)(23)(24) such as dehydrosqualene synthase and squalene synthase (31), which could also inhibit Plasmodium phytoene synthase, and cationic species (such as Ro 48-8071 and quinuclidines), some of which are known to inhibit Plasmodium cell growth (28,32). The structures of all 560 compounds are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These lipophilic bisphosphonates have far more potent activity both in vitro and in vivo than do conventional bisphosphonates in tumor cell-growth inhibition and γδ T-cell-activation assays (20, 21) as well as against malaria parasites (14). In this work, we elected to screen our in-house library of 560 prenyl-synthase inhibitors, developed over the past decade as anticancer drug leads and as antibacterials (20)(21)(22)(23)(24), for their activity in P. falciparum growth inhibition inside red cells. We discovered two potent leads, BPH-703 and BPH-811 (Scheme 1), lipophilic analogs of the commercial drugs zoledronate and risedronate, and determined their crystal structures bound to P. vivax…”
mentioning
confidence: 99%
“…For this purpose two non-commercial Horner reagents were self-made (Scheme 1). Diethyl ((methylsulfonyl)methyl)phosphonate 6 was prepared according to known procedures [7], while Horner reagent 9 was obtained by reacting half an equivalent of chlorodiethylphosphate with bis-lithiated 8 [8,9]. 3'-Silylated thymidine 12 was produced by a selective cleavage of the primary TBDMS group on 11 [10,11].…”
Section: Chemistrymentioning
confidence: 99%
“…The first committed step in the staphyloxanthin biosynthetic pathway proceeds through presqualene diphosphate and then dehydrosqualene, catalysed by CrtM (Pelz et al, 2005), and is very similar to that catalysed by SQS in plants, animals and some protozoa, as demonstrated in Fig. 1 (Song et al, 2009b). Liu et al (2008) recently observed that the crystal structure of S. aureus CrtM is very similar to that of human SQS used in cholesterol biosynthesis in humans (Liu et al, 2008).…”
Section: Discussionmentioning
confidence: 72%
“…Staphyloxanthin has been associated with enhancing bacterial survival in harsh environments and during infections (Giachino et al, 2001; Kahlon et al, 2010). The membrane pigment promotes resistance to reactive oxygen species (ROS) such as O 2 2 , H 2 O 2 and HOCl generated by host neutrophils (Lang et al, 2000;Clauditz et al, 2006;Song et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%